EFEKTIVITAS PROGRAM VEGIMPACT DALAM KERJASAMA INDONESIA-BELANDA TERHADAP PRODUKTIVITAS SAYURAN DI INDONESIA - Gusmar Yeni; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Indonesia is an agricultural country where most of the population works in agriculture, especially the horticulture and sub-sector of vegetable farming has the potential to increas farmers’ income through increasing the productivity. However the vegetable farming has some obstacles. To solve the obstacles or the problems and improve agriculture, Indonesia has carried out various ways, one of the many various ways is collaborating with superior countries in agriculture such as the Netherland. Vegimpact is an Indonesia-Netherland cooperation programme in agriculture to improve food security and increase vegetable productivity in order to increase farmers’ income and welfare. This study uses qualitative research methods that are descriptive analysis. The data used in the study are primary and secondary data. The primary data was obtained from websites of related institutions that have relevance to the research. And secondary data is obtained from literature studies such as books, scientific journals, theses, papers, newspapers, and documents or any related materials. The theoretical framework used in this research is the perspective of liberalism, level of analysis of the nation-state, and the theory is international cooperation. This study desribes the international cooperation carried out by Indonesia and the Netherland through the Vegimpact program to improve agriculture in Indonesia. to achieve its objectives, this program forms partnerships in Indonesia and intervenses through formulated work packages. The formulation of the work package for the Vegimpact program is adjusted to the Vegimpact problems that occur in the Indonesian agricultural sector, especially the horticulture sector and the vegetable farming sub-sector. The Vegimpact program helps Indonesia to improve food security, improve the private sector and also increase vegetable productivity in Indonesia.  Keywords: Vegimpact, International Cooperation, Agriculture, Productivity, Vegetable